The Role of the Work Environment as a Mediation for the Effect of Leadership Style on the Performance of Banking Institution Employees - R. Joko Sugiharjo; Rr. Niken Purbasari; Abdul Rahmat; Paijan Paijan (Dinasti International Journal of Management Science, 2023)
This study aims to determine the effect of leadership style on the performance of Bank Syariah Indonesia West Jakarta Branch employees and the role of the work environment as a mediator variable. This research was conducted using a descriptive causality approach and the PLS-SEM analysis method to test and explain the connectedness of the structural model. The sample technique used was purposive sampling and the number of samples obtained was 57 respondents. The results of this study are that leadership style has a positive and significant effect on the work environment, leadership style has a negative and insignificant effect on organizational performance, work environment has a positive and significant effect on organizational performance, and work environment as a mediator of leadership style influences employee performance positively and significantly.